2018
DOI: 10.1016/j.pneurobio.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

System biology approach intersecting diet and cell metabolism with pathogenesis of brain disorders

Abstract: The surge in meals high in calories has prompted an epidemic of metabolic disorders around the world such that the elevated incidence of obese and diabetic individuals is alarming. New research indicates that metabolic disorders pose a risk for neurological and psychiatric conditions including stroke, Alzheimer’s disease, Huntington’s disease, and depression, all of which have a metabolic component. These relationships are rooted to a dysfunctional interaction between molecular processes that regulate energy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 188 publications
(240 reference statements)
0
7
0
Order By: Relevance
“…In vitro cell culture experiments and rodent studies have shown that restriction or surfeit of macronutrients have reproducible effects on multiple epigenetic mechanisms on many different genes including those involved in metabolism and behaviour [167,168]. Metabolic perturbations are becoming known as a driving force for genomic and epigenomic alterations by which the effects of diet are saved in the genes [169]. Components of nutrient-rich dietary patterns including vitamins such as folate, biotin, B6 and B12; polyphenols such as curcumin, resveratrol and genistein [170]; and omega-3 fatty acids [171] have all been shown to influence epigenetic state through multiple mechanisms.…”
Section: Epigenetics Early Life and Maternal/paternal Diet Exposurementioning
confidence: 99%
“…In vitro cell culture experiments and rodent studies have shown that restriction or surfeit of macronutrients have reproducible effects on multiple epigenetic mechanisms on many different genes including those involved in metabolism and behaviour [167,168]. Metabolic perturbations are becoming known as a driving force for genomic and epigenomic alterations by which the effects of diet are saved in the genes [169]. Components of nutrient-rich dietary patterns including vitamins such as folate, biotin, B6 and B12; polyphenols such as curcumin, resveratrol and genistein [170]; and omega-3 fatty acids [171] have all been shown to influence epigenetic state through multiple mechanisms.…”
Section: Epigenetics Early Life and Maternal/paternal Diet Exposurementioning
confidence: 99%
“…The disturbances in cell energy metabolism pose a heavy toll for the maintenance of neuronal connectivity and function which can accelerate the pathogenesis of neurodegenerative diseases such as Alzheimer’s disease (Gomez-Pinilla and Yang, 2018 ). Synaptic communication is essential for neuronal function and cognition and highly demanding on energy such that disruptions in cell metabolism associated with fructose can heavily damage overall brain function, beyond simply cell survival.…”
Section: Fructose Metabolism and Alzheimer’s Diseasementioning
confidence: 99%
“…While the amyloid cascade hypothesis has not been discounted, other hypotheses are now receiving attention, including the role of cerebral insulin resistance and glucose hypometabolism (Neth and Craft, 2017 ), neuroinflammation (characterized by high cytokine levels at sites of tissue degeneration), synaptic dysfunction, and the role of mitochondrial dysfunction with alterations in intracerebral ATP levels (Demetrius et al, 2014 ; de la Monte, 2017 ; Cenini and Voos, 2019 ). There is also evidence that Alzheimer’s disease may be linked with obesity and diabetes, and with the western diet (Arvanitakis et al, 2004 ; Gomez-Pinilla and Yang, 2018 ). However, while obesity and diabetes are risk factors for Alzheimer’s disease (Arnold et al, 2018 ), Alzheimer’s disease may occur in the absence of these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…46,131,132 Finally, physical activity, dietary restriction, some foods, and social interaction could contribute to foster neuronal resilience and delay AD onset and progression by increasing brain BDNF expression. [133][134][135][136][137][138][139][140]…”
Section: Nerve Growth Factormentioning
confidence: 99%
“…Several drugs used for controlling AD risk factors such as diabetes, hypertension, hypercholesterolemia, depression, and stress may also enhance BDNF 46,131,132 . Finally, physical activity, dietary restriction, some foods, and social interaction could contribute to foster neuronal resilience and delay AD onset and progression by increasing brain BDNF expression 133–140 …”
Section: Neurotrophic Growth Factors In Ad Pathology and Treatmentmentioning
confidence: 99%